A design approach to fully compliant multistable mechanisms employing a single bistable mechanism. Issue 7 (3rd October 2021) - Gou, Yanjie; Chen, Guimin; Howell, Larry L.
Abstract: A fully compliant multistable mechanism is a monolithic structure that is capable of staying at multiple positions without power input, and has many applications including switches, valves, positioners. However, it is difficult to design such a mechanism because of the complexities of the multistable behavior, the practical stress limits and the buckling constraints. This paper discusses the design approach for fully compliant multistable mechanisms which employs a single bistable mechanism and several end-effectors connected in series. The force-displacement characteristics of the end-effectors are derived using the pseudo-rigid-body model. The design approach to the fully compliant multistable mechanism is provided to determine the design parameters for the flexible segments considering the critical buckling load and the bending strength. Two design examples are presented to demonstrate the feasibility of the approach.